2021
DOI: 10.1001/jama.2021.9883
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Prevalence of Diabetes and Control of Risk Factors in Diabetes Among US Adults, 1999-2018

Abstract: IMPORTANCEUnderstanding population-wide trends in prevalence and control of diabetes is critical to planning public health approaches for prevention and management of the disease. OBJECTIVE To determine trends in prevalence of diabetes and control of risk factors in diabetes among US adults between 1999-2000 and 2017-2018. DESIGN, SETTING, AND PARTICIPANTS Ten cycles of cross-sectional National Health and Nutrition Examination Survey (NHANES) data between 1999-2000 and 2017-2018 were included. The study sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
256
3
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(277 citation statements)
references
References 31 publications
14
256
3
4
Order By: Relevance
“…We found that the rates of hyperglycemic crises increased over time among patients with type 1 diabetes, from 43.30 per 1000 person-years in 2014 to 61.36 per 1000 person-years in 2019, consistent with previously described trends through 2015 16 and recent population-level data showing an overall worsening of glycemic control among patients with diabetes in the US. 23 , 24 There was no comparable temporal change in hyperglycemic crises rates among patients with type 2 diabetes. This persistent rise in rates of hyperglycemic crises among patients with type 1 diabetes underscores the urgency of improving glycemic control and diabetes management in this population.…”
Section: Discussionmentioning
confidence: 94%
“…We found that the rates of hyperglycemic crises increased over time among patients with type 1 diabetes, from 43.30 per 1000 person-years in 2014 to 61.36 per 1000 person-years in 2019, consistent with previously described trends through 2015 16 and recent population-level data showing an overall worsening of glycemic control among patients with diabetes in the US. 23 , 24 There was no comparable temporal change in hyperglycemic crises rates among patients with type 2 diabetes. This persistent rise in rates of hyperglycemic crises among patients with type 1 diabetes underscores the urgency of improving glycemic control and diabetes management in this population.…”
Section: Discussionmentioning
confidence: 94%
“…According to the International Diabetes Federation Atlas, 9th edition, 463 million adults worldwide live with diabetes as of 2019, with a prevalence rate of approximately 9.3% and an average annual growth rate of 51% ( 1 ). Diabetes easily leads to several complications that affect the prognosis of patients with diabetes ( 2 , 3 ). Approximately 4.2 million people worldwide died from diabetes or its complications in 2019, accounting for approximately 11.3% of all-cause deaths worldwide ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several longitudinal studies from North America, Europe, Asia and Australia have demonstrated that there has been a decline in chronic macrovascular complications of diabetes over the past few decades [1][2][3][4] as well as in all-cause and cardiovascular disease (CVD) death [5,6], reflecting improving CVD risk factor management [7][8][9]. Although these encouraging trends may be stabilizing and even reversing based on even more recent US data [10,11], there is still the possibility that other complications such as chronic kidney disease (CKD) may become more prominent as longevity increases [12].…”
Section: Introductionmentioning
confidence: 99%